BENTUK DINAMIKA PENYULUH AGAMA HINDU DI DKI JAKARTA - Suhardi, Untung; Tantre Awiyane, Wayan (IAHN Gde Pudja Mataram, 2022)
The existence of counselors there in Jakarta in accordance with regulation of the ministry of religion in conduct training in accordance with. Tasks and functionsThe development of globalization drove very quickly both in the technology and science. The acceleration is relating to the digital age and circumstances. Culture nevertheless, the implementation of development by extension in Jakarta is still experiencing the dynamics of especially in the form of the dynamics of. Extension workersA method of adopting phenomenology and interpretive. Paradigm. Types of data, the data kualititatif, data source, a source of the primary data, and secondary data. Data analysis techniques with a model of a cycle by reduction, data the presentation of data and data verification. The theory that is used is a theory strukturasi (Gidden). This research result that the dynamics of counselors is going on in Jakarta is going on a policy extension, (good regulations recruits, to scatter, and educated in areas), extension , extension worker program reproduction, social and the existence of extension